Täckning av plansilo - Johansson, Peter (2008)
With the increasing costs in concentrate the importance in producing ensilage with a high quality is becoming more and more important. To succeed with this goal it is of importance not only to harvest in the right period, but also to be able to store the ensilage without a decrease in quality and nutrional values. To maintain a good ensilage the covering of the ensilage must be carefully made. An unsuccessful covering causes mould to grow in the ensilage, which both increases the work load and also increases the amount of feed which is wasted. A bigger amount of spoiled feed also increases the risk of feeding spoiled feed to the cattle.